Isolation and partial characterization of Fc gamma-binding proteins of human leukocytes. - Kulczycki, A (1981)
We isolated and partially characterized three Fc-binding macromolecules from human leukocytes. Mononuclear cells from normal individuals and from five patients with chronic lymphocytic leukemia and neutrophils from normal donors were surface radiolabeled by using 125I and lactoperoxidase. After detergent solubilization of the cells, Fc gamma-binding macromolecules were purified by repetitive affinity chromatography under a variety of conditions and analyzed by sodium dodecyl sulfate (SDS)-polyacrylamide gel electrophoresis. Three radiolabeled macromolecules were isolated that retained specific ability to bind to Fc fragments. A 52,000-64,000-mol wt macromolecule was isolated from normal mononuclear and polymorphonuclear cells. A 43,000-mol wt band was characteristic of mononuclear cells, particularly from patients with chronic lymphocytic leukemia. A 33,000-mol wt molecule could be obtained from normal leukocytes under conditions that suggest it might be a proteolytic fragment.